Gambaran Sarana Sanitasi Masyarakat Kawasan Pesisir Pantai Dusun Talaga Desa Kairatu Kecamatan Kairatu Kabupaten Seram Bagian Barat Tahun 2014 - Sholehah Imroatus; Mulyadi Mulyadi; Maryam Lihi (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2015)
Back Ground. Sanitation is means of collection and disposal of excreta and society`s hygien water disposal so it is not danger for society. Objective: To know descriptive of sanitation equip-ment for coastal area society at talaga city side kairatu village kairatu subdistrict west of seram 2014. Method. This research use descriptive research. Sample has taken by total sampling. There are 123 family as responden. Result. There are 3 responden (8,6%) have clean water accourding hy-giene criteria, there are 32 responden (91,4%) dosen`taccourding hygiene criteria. There are 4 (13,8%) responden have privy variable accourding criteria, there are 25 responden (86,2%) dosen`taccourding privy criteria. There are 3 responden (20%) have SPAL variable accourding crite-ria, there are 12 responden (80%) dosen`taccourding criteria. And there are 4 responden (12,9%) have landfills variable accourding criteria, there are 26 responden (87,1%) dosen`taccourding crite-ria.Conclution. Hygiene water, privy, SPAL, landfills disposal that can descript it dosen`taccourding with criteria so need good sanitation for coastal society at Talaga city side Kairatu village West of Se-ram.Keyword. Sanitation for coastal society, descriptive of hygiene water sanitation, privy, SPAL, and